UPAYA PENINGKATAN KEMAMPUAN MEMBACA SISWA MENGGUNAKAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) DI KELAS 2 UPT SD NEGERI 75 BENTANG - Haryanti Nurasmi; Dwi Astuti Arifin; Muhammad Akhir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the reading skills of grade 2 students at UPT SD Negeri 75 Bentang through the SAS method, a systematic and structured approach to developing reading skills by understanding language structure and sentence analysis. This research employs Classroom Action Research (CAR) to identify learning issues, implement necessary changes, and evaluate effectiveness. The results show that the SAS method effectively enhances students' reading skills, demonstrating significant improvements in sentence structure comprehension and vocabulary.Therefore,the SAS method is concluded to bea n effective alternative for enchanging elementary school student’s resding skills,worthy of consideration by teachers for reading instruction.